The Relationship Between Performance Management and The Quality of Animal, Fish, and Plant Quarantine Services - Beniawan, Apris; Poltak Sinambela, Lijan (International Journal of Management Science and Information Technology, 2025)
Effective performance management is a key factor in achieving organizational goals, including in the context of animal, fish, and plant quarantine services. This study aims to explore the relationship between performance management and the quality of quarantine services, focusing on relevant challenges and improvement strategies. A qualitative descriptive research method was used to collect data through observations, interviews, and documentation at the Indonesian Quarantine Agency office. The results show that integrated performance management can improve the effectiveness and efficiency of services, although challenges remain, such as limited infrastructure, competency gaps in human resources, and bureaucratic complexity. The implementation of digital technology and human resources training are important strategies to enhance service quality. In addition, collaboration with stakeholders and the adoption of global best practices can strengthen Indonesia's position in international trade. This study provides policy recommendations to improve performance management and quarantine service quality, expected to have significant social and economic impacts on the agriculture, fisheries, and forestry sectors in Indonesia.